2019
DOI: 10.1111/avsc.12435
|View full text |Cite
|
Sign up to set email alerts
|

Effects of woody species encroachment and fire on vegetation and the soil seed bank in dry grasslands of Transylvania

Abstract: Questions: (a) In which ways do woody species encroachment and fire affect vegetation and seed bank composition, structure and diversity in Transylvanian dry grassland; (b) do native and non-native woody species differ with respect to their impact on grassland community composition and structure; (c) is burning useful to control woody species encroachment; and (d) can soil seed banks contribute to the restoration of grasslands in Transylvania? Location: Transylvania, Romania. Methods: We collected data on vege… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 69 publications
1
7
0
Order By: Relevance
“…Overall, our results indicate that shrub encroachment influenced vegetation composition more than wildfire (see also Görzen et al, 2019). Grassland recovery in burnt juniper plots following the wildfire was surprisingly fast and took place within the timeframe of our study.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Overall, our results indicate that shrub encroachment influenced vegetation composition more than wildfire (see also Görzen et al, 2019). Grassland recovery in burnt juniper plots following the wildfire was surprisingly fast and took place within the timeframe of our study.…”
Section: Discussionsupporting
confidence: 78%
“…Our results support considerable and long‐lasting effects of juniper encroachment on species composition during the transformation of grasslands into woodlands (Gehring & Bragg, 1992; Linneman & Palmer, 2006; Ganguli et al, 2008). Furthermore, invasions of native shrubs have been reported to induce substantial compositional changes in several ecosystems, such as in Southwestern Australian heathlands (Shackelford et al, 2015), in South American savanna wetlands (Barbosa da Silva et al, 2016), in Indian montane grasslands (Srinivasan, 2011), and also in European dry grasslands (Maestre et al, 2009; Görzen et al, 2019). We also showed that the expansion of juniper patches led to an increase in the number of plant species associated with Juniper plots.…”
Section: Discussionmentioning
confidence: 99%
“…In the last few decades, socio-economic transformations in the Alps have led, in some areas, to the decline of livestock farming and agriculture and consequently to land abandonment [7,8]. This process opened the way to woody shrub and tree encroachment, which, in turn, has the potential to modify the ecosystem structure and function, with both negative and positive consequences for ecosystem services [9][10][11] and biodiversity [12,13]. Generally, the woody encroachment of grasslands causes an alteration of microclimatic conditions and a reduction of herbaceous cover, which contribute to the consequent decrease of species richness in the long-term, e.g., [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…This process opened the way to woody shrub and tree encroachment, which, in turn, has the potential to modify the ecosystem structure and function, with both negative and positive consequences for ecosystem services [9][10][11] and biodiversity [12,13]. Generally, the woody encroachment of grasslands causes an alteration of microclimatic conditions and a reduction of herbaceous cover, which contribute to the consequent decrease of species richness in the long-term, e.g., [12][13][14]. Nevertheless, this observation depends on the encroachment stage and the relative woody cover.…”
Section: Introductionmentioning
confidence: 99%
“…C. Craioveanu​, I. Muntean, E. Ruprecht, R. I. Băncilă, R.I., A. Crișan, L. Rákosy (unpublished) pointed out that spatio‐temporal changes in land use type and intensity in Transylvanian basiphilous dry grasslands affect plant and animal diversity as well, and that butterfly diversity is the highest in mown grasslands. Numerous studies showed that abandonment is linked with diversity loss compared to grazing and mowing (e.g., Wahlman & Milberg, 2002; Bossuyt et al, 2006; Enyedi et al, 2008; Görzen et al, 2019). In contrast, our results suggest that in some cases short‐term abandonment may not be as detrimental in terms of species richness.…”
Section: Discussionmentioning
confidence: 99%